Correction: High photocurrent in oligo-thienylenevinylene-based small molecule solar cells with 4.9% solar-to-electrical energy conversion. Issue 22 (14th June 2015) - Montcada, Núria F.; Domínguez, Rocío; Pelado, Beatriz; Cruz, Pilar de la; Palomares, Emilio; Viterisi, Aurelien; Langa, Fernando
<x xml:space="preserve">Abstract</x> Correction for 'High photocurrent in oligo-thienylenevinylene-based small molecule solar cells with 4.9% solar-to-electrical energy conversion' by Núria F. Montcada et al., J. Mater. Chem. A, 2015, DOI: 10.1039/c5ta01632k.